2011
DOI: 10.1038/ejhg.2011.6
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of genetic associations of CDKAL1 and HHEX with susceptibility of type 2 diabetes mellitus by gender

Abstract: We examined the genetic associations of previously identified sequence variants with type 2 diabetes mellitus (T2DM) and its potentially genetic heterogeneity by gender in a large-scale cohort. A total of 613 T2DM patients and 8221 control subjects from the Korea Association REsource (KARE) cohort were included in the analysis of genetic association of T2DM with 33 nucleotide polymorphic markers identified by previous studies. The association analysis was further conducted with data partitioned by gender. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 27 publications
4
22
1
Order By: Relevance
“…These results suggest collective genetic effects, but not necessarily individual genetic effects, were comparable between genders. For example, female-specific associations have been reported between GLU and nucleotide variants of the gene encoding CDKAL1 and HHEX (Ryoo et al 2011) and between WHR and those of GRB14, LYPLAL1, and ADAMTS9 genes (P<0.05) (Heid et al 2010). The correlation coefficients estimated from our current study also showed that gender differences in individual genetic effects were not negligible, even for quantitative traits without heterogeneity.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…These results suggest collective genetic effects, but not necessarily individual genetic effects, were comparable between genders. For example, female-specific associations have been reported between GLU and nucleotide variants of the gene encoding CDKAL1 and HHEX (Ryoo et al 2011) and between WHR and those of GRB14, LYPLAL1, and ADAMTS9 genes (P<0.05) (Heid et al 2010). The correlation coefficients estimated from our current study also showed that gender differences in individual genetic effects were not negligible, even for quantitative traits without heterogeneity.…”
Section: Discussionsupporting
confidence: 62%
“…Genotypes of SNPs on sex chromosomes were excluded from the analysis. Unobserved SNP genotypes for each individual in the cohort were imputed with the Japanese and Chinese HapMap phase 2 haplotype panel using the IMPUTE software program (Ryoo et al 2011). Data from 7,172 individuals were used in our study after removing data from related individuals with a relationship coefficient of 0.025 or greater.…”
Section: Subjects and Datamentioning
confidence: 99%
“…The smaller number of male subjects may account for the difference. However, we could not exclude the contribution of possible genetic heterogeneity between men and women [29], and between Chinese and Japanese population.…”
Section: Discussionmentioning
confidence: 96%
“…In 2010, Zhou et al reported that the HHEX rs5015480 C allele frequency showed a marginally signi cant statistics difference between T2DM and control group in Chinese population [31] In the same year, Han et al also reported that the rs5015480C allele was signi cantly associated with T2DM in the Chinese population [24]. However, a study in 2011 reported that further analysis revealed that the sequence variant (rs5015480) on HHEX was associated with the susceptibility of T2DM in females, but not in males Korean population [32].Few years later, in 2013, this association of rs5015480T allele, with T2DM had been validated in Chinese She population [28]. In Chinese She population, the rs5015480T allele frequency with 52.7-59.7% is higher than other Chinese population [28].…”
Section: Discussionmentioning
confidence: 99%